Penggunaan Alat Peraga Biologi untuk Meningkatkan Motivasi dan Hasil Belajar Kognitif Siswa - Hasanah, Marlia; Ulviani, Ida (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
The purpose of this study was to determine the increase in students' motivation and cognitive learning outcomes through the use of biology teaching aids. The place of this research is at SMP Negeri 9 Palangka Raya for the 2019/2020 academic year. This type of research is Classroom Action Research (CAR) using a quantitative and qualitative approach which is carried out in 2 cycles. The instrument used was an observation sheet on the implementation of the learning implementation plan, a questionnaire sheet, and a cognitive learning outcome test sheet. Collecting data in the form of observation data, questionnaires, and tests of cognitive learning outcomes. The data analysis technique used observation of the implementation of the learning implementation plan, motivational questionnaire data, cognitive learning outcomes data, individual mastery, and classical completeness. The results of this study are quantitative data and qualitative data. This is indicated by an increase in the score for the implementation of the learning implementation plan in the first cycle as many as 12 with a very good category. In the second cycle as many as 13 implementations with a very good category. In the data on student learning motivation, the number of students who fall into the highly motivated category is 19 people and 4 people are motivated with a percentage of 83% and the category is highly motivated. In the second cycle, 22 students were included in the highly motivated category and 1 person was motivated with a percentage of 84.7% and the highly motivated category. Therefore, the results of the evaluation analysis in the first cycle with a percentage of 60%. In the second cycle increased by 86.9%. So, it can be concluded that the use of biology teaching aids can increase motivation and cognitive learning outcomes of class VIIB students of SMP Negeri 9 Palangka Raya for the 2019/2020 academic year.